Integrating Reflective Practice and Personalised Feedback in Students’ Learning Experience - Mohamad Azhari, Abu Bakar; Kartini, Abdul Ghani; Ida Juliana, Hutasuhut; Jamayah, Saili; Norehan, Zulkipli; Nor Hasniah, Ibrahim
The innovative idea started from the scholarship of teaching and learning grant investigating the growth of reflective practice in psychology undergraduate students. Reflectivepracticeincreasestheactiveengagementofstudentsandpersonalownershipofself-development,throughtheuseofpersonalisedfeedbackasatoolforimprovinginstructionalpractice.Theprocessofreflectivepracticeandpersonalisedfeedbackrequirecontinuouseffortandattempttoscaffoldstudents’learningexperience.Thisstudyexaminesthequality of reflective practice writing which was done via the course’s E-learning page by providing personalised feedback based on five levels of reflective practice criteria.